Cytotoxic, antioxidant, and antiglycation activities, and tyrosinase inhibition using silver nanoparticles synthesized by leaf extract of Solanum aculeatissimum Jacq - Silva, Regildo Márcio Gonçalves da [UNESP]; Do Nascimento Pereira, Isabelly [UNESP]; Camargo Zibordi, Laura [UNESP]; Pereira Rosatto, Pedro Augusto [UNESP]; Oliveira Granero, Filipe [UNESP]; Malaguti Figueiredo, Célia Cristina [UNESP]; Leopoldo Constantino, Carlos José [UNESP]; da Silva Martin, Cibely [UNESP]; Eloizo Job, Aldo [UNESP]; Nicolau-Junior, Nilson; Pereira Silva, Luciana (Taylor & Francis, 2024)
The present study aimed to determine the biological properties of an extract of Solanum aculeatissimum aqueous extract (SaCE) alone as well as silver nanoparticles (AgNPs) generated by green synthesis utilizing S. aculeatissimum aqueous extract (SaCE). These synthesized SaCE AgNPs were characterized using UV-VIS spectrophotometry, scanning transmission electron microscopy (TEM), energy dispersive spectroscopy (EDS), zeta potential (ZP), dynamic light scattering (DLS). Determination of total polyphenols, flavonoids, saponins content was conducted. In addition, high performance liquid chromatography-mass spectrometry (HPLC-MS) was employed to identify constituents in this extract. Antioxidant activity was determined by DPPH radical scavenging and ferric ion reducing power (FRAP) methods. Antiglycation activity was demonstrated through relative mobility in electrophoresis (RME) and determination of free amino groups. The inhibitory activity on tyrosinase was also examined. Molecular docking analyses were performed to assess the molecular interactions with DNA and tyrosinase. The antitumor activity SaCE was also measured. Phytochemical analysis of SaCE and AgNPs showed presence polyphenols (1000.41 and 293.37 mg gallic acid equivalent/g), flavonoids (954.87 and 479.87 mg rutin equivalent/g), saponins (37.89 and 23.01% total saponins), in particular steroidal saponins (aculeatiside A and B). Both SaCE and AgNPs exhibited significant antioxidant (respectively, 73.97%, 56.27% in DPPH test, 874.67 and 837.67 μM Trolox Equivalent/g in FRAP test) and antiglycation activities (72.81 and 67.98% free amino groups, results observed in RME). SaCE and AgNPs presented 33.2, 36.1% inhibitory activity on tyrosinase, respectively. In silico assay demonstrated interaction between steroidal saponins, DNA or tyrosinase. SaCE exhibited antitumor action against various human tumor cells. Data demonstrated that extracts SaCE alone and AgNPs synthesized from SaCE presented biological properties of interest for application in new therapeutic formulations in medicine.
Keywords: Ageing; Anti-tyrosinase; antitumor; Molecular docking; saponins